Concurrent improvement of the metabolic syndrome and lower urinary tract symptoms upon normalisation of plasma testosterone levels in hypogonadal elderly men - A. Haider (2018)
Central obesity in adulthood, the metabolic syndrome, erectile failure and lower urinary tract symptoms (LUTS) are all associated with lower-than-normal testosterone levels, although the relationship between testosterone and LUTS appears weak. The metabolic syndrome is associated with an overactivity of the autonomic nervous system. Alternatively, the metabolic syndrome is associated with markers of inflammation, such as C-reactive protein (CRP), maybe signalling intraprostatic inflammation. A large cohort of 95 middle-aged to elderly hypogonadal men (T levels 5.9-12.1 nmol l-1) were treated with parenteral testosterone undecanoate and its effects on the metabolic syndrome [waist circumference, cholesterol, CRP and LUTS [residual bladder volume (RBV), International Prostate Symptoms Score (IPSS), prostate volume, prostate-specific antigen (PSA)]] were evaluated. Along with the improvements of the metabolic syndrome, there was a significant decline of the values of the IPSS, RBV and CRP. There was a (low) level of correlation between the decline of waist circumference and residual volume of urine but not with IPSS and prostate size. Along with the improvement of the metabolic syndrome upon testosterone administration, there was also an improvement of the IPSS and of RBV of urine and CRP. The mechanism remains to be elucidated. © 2009 Blackwell Publishing Ltd.